The Impact of COVID-19 Pandemic on the Academic Performance of Veterinary Medical Students - Mahdy, Mohamed A. A. (Frontiers in Veterinary Science, 2020)
Many universities and colleges worldwide suspended classroom teaching due to the novel coronavirus pandemic and switched to online teaching. The current cross-sectional study was carried out to analyze the impact of COVID-19 lockdown on the academic performance of veterinary medical students and researchers. Veterinary medical students and researchers were invited to answer an online google form questionnaire. A total of 1392 participants were from 92 different countries answered the questionnaire with response rate of 94.1%. The data showed that COVID-19 pandemic lockdown affected the academic performance of most participants (96.7%) with varying degrees. The mean evaluation scores for the online education in general was 5.1 ± 2.4 while that for the practical parts was 3.6± 2.6. Although online education provides an opportunity for self-study. The main challenge that online education faces in veterinary medical science is how to give practical lessons. Since most of the subjects are practical; therefore, it is not easy to learn it online. Students think that it is difficult to fulfill the veterinary competencies only with online education system. Online education can be improved by making it more interactive, showing medical procedures in real situations, giving concise information, and providing 3D virtual tools to mimic the real situation.